A performance comparison of the paediatric i‐gel™ with other supraglottic airway devices. (3rd September 2014) - Smith, P.; Bailey, C. R.
Summary We performed a review of published literature comparing the i‐gel™ with other supraglottic airway devices in children. Sixty‐two articles were identified following a literature search; we included data from 14 randomised controlled trials and eight observational studies that compared i‐gel sizes 1–2.5 with other commonly used, equivalently‐sized, devices. The primary outcome in most studies was oropharyngeal leak pressure. In the 14 randomised trials the i‐gel performed the same as the comparator device in five trials, significantly better in eight studies (p < 0.05) and significantly worse in one (p < 0.01). Seven studies assessed fibreoptic views of the larynx through the device; two found significantly better views through the i‐gel. Three studies reported a shorter insertion time for the i‐gel, whereas two reported a longer time. Insertion success rate, gastric tube placement and complications were similar for all the devices. Seven of the eight observational studies measured average oropharyngeal leak pressures of 20–27 cmH2O and all had first‐time insertion success rates exceeding 90%. We conclude that the i‐gel is at least equivalent to other supraglottic airway devices currently available for use in children, and may enable a higher oropharyngeal leak pressure and an improved fibreoptic view of the glottis.